Biochemical characterisation of a new thermotolerant L-asparaginase produced by Cunninghamella echinulata PA3S12MM isolated from the Atlantic Forest - Simone Von Groll; Leticia Claudia da Silva; Pedro Henrique Nascimento Souza; Wállison Justino da Silva; Thaís Duarte Bifano; José Luis da Conceição Silva; Rita de Cássia Garcia Simão; Simão; Marina Kimiko Kadowaki; Alexandre Maller (Archives of Microbiology, 2026)
L -asparaginase is an amidohydrolase enzyme that catalyses the hydrolysis of L-asparagine into L-aspartic acid and ammonia. This enzyme has significant biotechnological applications, functioning as an antineoplastic agent in the pharmaceutical industry and as a tool for reducing acrylamide formation in the food industry. This study aimed to identify a filamentous fungus strain capable of synthesizing a new L -asparaginase and to perform its biochemical characterisation. Among the fungal isolates screened using plate assays and submerged fermentation, Cunninghamella echinulata strain PA3S12MM was identified as a promising L -asparaginase producer. The highest enzymatic induction was achieved using 5% (w/v) glucose as the carbon source and 0.4% (w/v) chicken feather as an agro-industrial nitrogen source, under incubation for 120 h. The enzyme exhibited an apparent K m app of 0.011 mmol L⁻¹ and a V max app of 126.5 mmol L⁻¹ min⁻¹ for the hydrolysis of L-asparagine. Partial purification revealed that the enzyme displayed optimal activity at pH 7.0 and a temperature of 85 °C. In terms of substrate specificity, the enzyme demonstrated 100% relative activity toward L-asparagine and 32.9% toward L-glutamine. Enzymatic activity was enhanced by β-mercaptoethanol but inhibited by Mn²⁺, L-cysteine, and dithiothreitol (DTT). These findings suggest that C. echinulata PA3S12MM is a promising candidate for large-scale biotechnological production of a new fungal L -asparaginase, with biochemical indicators of potential for applications in both pharmaceutical and food industries.

Exploring biodegradable alternatives: microorganism-mediated plastic degradation and environmental policies for sustainable plastic management - Rita de Cássia Garcia Simão; Paula Maria Carneiro Rocha; Júlia Thays Kava Martins; Maurício Turkiewicz; Jacqueline Plewka; José Luis da-Conceição Silva; Alexandre Maller; Marina Kimiko Kadowaki; Álvaro Pereira Sampaio Costa-Júnior (Archives of Microbiology, 2024)

Biopolishing of denim by the recombinant xylanase II of Caulobacter crescentus - Débora Jacomini; Larissa Bussler; José Luis da-Conceição Silva; Alexandre Maller; Marina Kimiko Kadowaki; Rita de Cássia Garcia Simão (Brazilian Journal of Microbiology, 2023)

Prebiotic effect of sorghum biomass xylooligosaccharides employing immobilized endoxylanase from Thermomyces lanuginosus PC7S1T - Andreza Gambelli Lucas Costa Nascimento; Érica Sabrina Zuppa; Maiara Zonin; Gabriela Furlaneto Sanchez de Sousa; Diandra de Andrades; Marco Antônio Záchia Ayub; Alexandre Maller; José Luis da Conceição Silva; Rita de Cássia Garcia Simão; Marina Kimiko Kadowaki (Brazilian Journal of Microbiology, 2022)

Spike protein of SARS-CoV-2 variants: a brief review and practical implications - Kattlyn Laryssa Candido; Caio Ricardo Eich; Luciana Oliveira de Fariña; Marina Kimiko Kadowaki; José Luis da Conceição Silva; Alexandre Maller; Rita de Cássia Garcia Simão (Brazilian Journal of Microbiology, 2022)

Cloning, expression and characterization of C. crescentus xynA2 gene and application of Xylanase II in the deconstruction of plant biomass - Débora Jacomini; Larissa Bussler; Juliana Moço Corrêa; Marina Kimiko Kadowaki; Alexandre Maller; José Luis da-Conceição Silva; Rita de Cássia Garcia Simão (Molecular Biology Reports, 2020)

Caulobacter crescentus β-Xylosidase II Is Highly Tolerant to Inhibitors Present in Fermentative Processes Involving Lignocellulosic Biomass - Amanda Alves Silva; Juliana Moço Corrêa; Alexandre Maller; Marina Kimiko Kadowaki; Luciane Sene; Rinaldo Ferreira Gandra; José Luiz da-Conceição Silva; Rita de Cássia Garcia Simão (BioEnergy Research, 2020)

Upregulation of the clpB gene in response to heat shock and beta-lactam antibiotics in Acinetobacter baumannii - Waleska Yana Lazaretti; Elaine Luzia dos Santos; José Luis da-Conceição Silva; Marina Kimiko Kadowaki; Rinaldo Ferreira Gandra; Alexandre Maller; Rita de Cássia Garcia Simão (Molecular Biology Reports, 2020)

Analysis of the xynB5 gene encoding a multifunctional GH3-BglX β-glucosidase-β-xylosidase-α-arabinosidase member in Caulobacter crescentus - Priscila Innocenti Justo; Juliana Moço Corrêa; Alexandre Maller; Marina Kimiko Kadowaki; José Luis da Conceição-Silva; Rinaldo Ferreira Gandra; Rita de Cássia Garcia Simão (Antonie van Leeuwenhoek, 2015)

Functional properties of a manganese-activated exo-polygalacturonase produced by a thermotolerant fungus Aspergillus niveus - Alexandre Maller; Tony Marcio da Silva; André Ricardo de Lima Damásio; Izaura Yoshico Hirata; João Atílio Jorge; Hector Francisco Terenzi; Maria de Lourdes Teixeira de Moraes Polizeli (Folia Microbiologica, 2013)

Purification, partial characterization, and covalent immobilization–stabilization of an extracellular α-amylase from Aspergillus niveus - Tony Marcio Silva; André Ricardo de Lima Damásio; Alexandre Maller; Michele Michelin; Fabio M. Squina; João Atílio Jorge; Maria de Lourdes Teixeira de Moraes Polizeli (Folia Microbiologica, 2013)

Endo-xylanase GH11 activation by the fungal metabolite eugenitin - Willian J. Andrioli; André R. L. Damásio; Tony M. Silva; Vinícius B. da Silva; Alexandre Maller; N. P. D. Nanayakkara; Carlos H. T. P. Silva; Maria L. T. M. Polizeli; Jairo K. Bastos (Biotechnology Letters, 2012)

Tunicamycin inhibition of N-glycosylation of α-glucosidase from Aspergillus niveus: partial influence on biochemical properties - Tony Márcio Silva; Fausto Bruno Dos Reis Almeida; André Ricardo de Lima Damásio; Alexandre Maller; Michele Michelin; João Atílio Jorge; Ebert Seixas Hanna; Maria Cristina Roque-Barreira; Héctor F. Terenzi; Maria de Lourdes Teixeira de Moraes Poliz (Biotechnology Letters, 2010)

Purification and biochemical characterization of a novel α-glucosidase from Aspergillus niveus - Tony Marcio da Silva; Michele Michelin; Andre Ricardo de Lima Damásio; Alexandre Maller; Fausto Bruno Dos Reis Almeida; Roberto Ruller; Richard John Ward; José Cesar Rosa; João Atilio Jorge; Héctor Francisco Terenzi; Maria de Lourdes Teixeira de Moraes Poliz (Antonie van Leeuwenhoek, 2009)